Digital Currencies Trading under Polish and EU Public Law - Bałdowski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
Digital currencies are a worldwide phenomenon gaining an increasing interest among investors, economists and legal scholars. They are used mainly as a new mean of ex-change and as a new way of investing funds, since the rapid changes in their value allow to gain extraordinary profits. Up to this point the legal status of digital currencies has not been clearly established under neither Polish nor EU public law, although some of the existing regulations may be indirectly applied to them. Under current regulations digital currencies cannot be treated as a legal mean of payment, as an electronic money nor a financial instrument. Creation of a complex regulation regarding digital currencies and granting administrative authorities supervisory powers over their trade seems to be necessary. Because of the evolution of financial markets, classifying digital currencies as financial instruments is a possible way of regulating their trade.